Agglomeration of Manufacturing Industrial, Economic Growth, And Interregional Inequality in South Sumatra, Indonesia - Mukhlis, Mukhlis; Robiani, Bernadette; Marwa, Taufiq; Chodijah, Rosmiyati (International Journal of Economics and Financial Issues, 2017)
Industrial agglomeration has Become common discussion topic, particularly in relation to economic growth and the reduction of regional inequality between regions. The phenomenon that Occurs at this time that the agglomeration of manufacturing industries in South Sumatra has not fully happened. However, the determination of South Sumatra Province as one of the central regions of industrial growth reflects the high economic growth and low levels of income inequality are the effects of the agglomeration of manufacturing industry. The analysis technique used the simultaneous model with panel data interregional in South Sumatra with two-stage least square (2SLS) approach, during the period 2004-2014. The potential agglomeration of manufacturing industry is calculated using the Balassa index, while regional inequality calculated using Williamson index. The results Showed that, (1) economic growth (G), income inequality (IW) and population (POP) exhibited Significantly effect on agglomeration of manufacturing industry (IB); (2) agglomeration of manufacturing industry, population, per capita income (YCapt) and a per capita income of the previous year (YCapt-1) a significant effect on economic growth; and (3) economic growth (Gt), economic growth in the previous year (Gt-1) and agglomeration of manufacturing industry significant influence on income inequality. Keywords: Agglomeration, Economic Growth, Regional Inequality JEL Classification: L68